The Book as an Editorial Dilemma. The Cracovian Publishers and their Aesthetic Perspectives. - Sikorska, Joanna (Acta Academiae Artium Vilnensis, 2021)
The purpose of this article is to demonstrate the aesthetic attitudes of two major publishers active in Cracow in the second half of the 16th century: Mikołaj Szarfenberger (1519--1606) and Jan Januszowski (1550-1613). In the dedications and prefaces, they presented a broad view of their editorial efforts and the circumstances in which their publications were created. A critical analysis of these texts indicates editors' growing awareness of how complex the matter of the "art of the book" truly was.